Financial Crises, Poverty, and Income Distribution. (IMF Working Papers; Working Paper ;, 2002)
Developing and transition economies are prone to financial crises, including balance of payments and banking crises. These crises affect poverty and the distribution of income through a variety of channels: slowdowns in economic activity, relative price changes, and fiscal retrenchment, among others. This paper deals with the impact of financial crises on the incidence of poverty and income distribution, and discusses policy options that can be considered by governments in the aftermath of crises. Empirical evidence, based on both macro- and microlevel data, shows that financial crises are associated with an increase in poverty and, in some cases, income inequality. The provison of targeted safety nets and the protection of specific social programs from fiscal retrenchment remain the main short-term propoor policy responses to financial crises.